Comparison of readmission and complication rates between traditional sleep surgery and hypoglossal nerve stimulation. Issue 5 (22nd September 2022) - Nord, Ryan; Fitzpatrick, Thomas; DeShazo, Jonathan P.; Reiter, Evan R.
Abstract: Objective: This study aims to compare readmission and complication rates between hypoglossal nerve stimulation (HNS) and traditional sleep surgery (TSS) in the 90‐day postoperative period using a federated electronic health record (EHR) database. Methods: We queried TriNetX, a global federated health research network providing access to EHR data from approximately 70 million patients in 49 large health care organizations to identify individuals who underwent either HNS or TSS for obstructive sleep apnea (OSA) from April 2014 to March 2021. Propensity scores based on demographics and obesity were used to balance groups. We compared the frequency of readmission/representation and surgical‐related complication rates between cohorts. Results: After propensity score matching of HNS versus palatal surgery ( n = 1014 in each cohort) and HNS versus multilevel surgery ( n = 374 in each cohort), we found palatal and multilevel surgery had a significantly higher risk of readmission versus HNS. (12% vs. 4%, p < .0001). Palatal surgery complication rate was also higher than HNS (21% vs. 2%, p < .0001). Multi‐level surgery results were similarly higher (22% vs. 3%, p < .001). The most common diagnoses at ER readmission for TSS were procedural complications and pain, while common diagnoses for HNS readmission were general complaints such as malaise and headache. Conclusions: Hypoglossal nerve stimulation has lower risk of readmission and postoperative complications than traditional sleep surgery as demonstrated in a large research network database analysis. Level of Evidence: 3. Abstract : This study aims to compare readmission and complication rates between hypoglossal nerve stimulation, a novel implantable neurostimulation system to treat selected CPAP‐intolerant obstructive sleep apnea by stimulating the distal branches of the hypoglossal nerve, against traditional sleep surgery methods in the 90‐day postoperative period using a federated electronic health record database. We found that hypoglossal nerve stimulation has a significantly lower risk of readmission and postoperative complications than traditional sleep surgery.